Pengaruh Kualitas Pelayanan dan Promosi Online Terhadap Keputusan Penggunaan Jasa (Studi Kasus di R.A Wedding Lamongan) - Kuni Anisata Aini (BIMA : Journal of Business and Innovation Management, 2020)
The purpose of this research is to find presence or absence the influence of Service quality and the online promotion on the service use desicions ( case study on the R.A wedding Lamongan ). Type of this research is using quantitative method. Sampling technique that using by the research is non probably sampling techniques in a way compare incidental sampling with a sample of 80 costumers. Data collection in this research is using questionnaire, interview, documentation, and observation. In the process of data analysis the researcher using statistical method to validity and reability the data, classic assumption test, hypothesis with multiple linear formula. Finding of the research indicate that : (1) basicly, Servive quality give impact positivity on the service use decisions in R.A wedding Lamongan (2) The online promotion has significant effect in the service use decisions in R.A wedding Lamongan. (3) Service quality and the online promotion has influence in to service use decisions on the R.A wedding Lamongan.